First Report of Colletotrichum tropicale Causing Anthracnose on Pitaya ( Hylocereus costaricensis ) in Brazil - Inokuti, Eliane Mayumi; Silva, Diene Elen Miranda da; Almeida, Mirla Maria Mesquita; Oliveira, Jamile Rabêlo; Andrade, Israel Lopes de; Silva, Christiana de Fátima Bruce da; Corrêa, Márcio Cleber de Medeiros; Lima, Cristiano Souza (Plant disease, 2024)
Pitaya, , is a species of the Cactaceae family and originated in the Americas (Ortiz & Livera, 1995). It has been cultivated in Brazil and has shown a great potential for fruit production and is currently present in several markets (Faleiro et al. 2021). In July 2018, infected plants of pitaya with symptoms of anthracnose were obtained from an orchard in Fortaleza, Ceará Brazil, (3°44'24.5"S 38°34'30.8"W), with 50% disease incidence. The symptoms observed consisted of well-defined and depressed stains, that initially appeared as reddish-orange spots and were surrounded by a border of dark-brown color. As the lesion progressed, the center became light brown or whitish in color, with black dots appearing later. Four cladodes were collected with anthracnose symptoms. The pathogen was isolated from symptomatic cladodes, which were surface disinfected with 1% v/v NaClO and 70% v/v ethanol, rinsed with sterile distilled water, transferred onto potato dextrose agar (PDA) medium and incubated under a light/dark (12h/12h) photoperiod. Two isolates were recovered from the lesions on cladodes. Pure cultures were obtained from single conidia produced on colonies grown on PDA medium, using an inoculation needle under a microscope. Colonies on PDA exhibited white aerial mycelia with an orange conidial mass. The colonies were light grey in the front and light orange in the reverse of the plate. Morphological features suggested that the isolates had the same characteristics as previously described for spp. (Weir et al., 2012). In order to identify the species of the isolates, the genomic DNA of UFCM 0684 and UFCM 0685 isolates was extracted using the CTAB method and the ITS region, TUB2, ACT, GS, GAPDH gene fragments were amplified. PCR products were sequenced and the resulting sequences were submitted to phylogenetic analyses based on maximum likelihood for the combination of the genes. The isolates grouped within with 99% bootstrap support. The sequences obtained in this study were deposited in GenBank as ACT (accession no. OL799311, OL799312), TUB2 (OL799313; OL799314), GAPDH (OL799315, OL799316), GS (OL799317; OL799318) and ITS (OL799319; OL799320). After that, the UFCM 0685 isolate was selected to study for further characterization. Conidia (n = 50) were 13.7 (length) × 4.7 μm (width) in average, hyaline, aseptate and cylindrical. To complete Koch's postulates, pathogenicity tests were performed in moist chamber for one week at 25°C with 80% relative humidity on a 12 h fluorescent light/dark photoperiod. The cladodes were wounded using a sterilized needle and inoculated with 10 µl of a conidial suspension (1 × 106 conidia/ml) on three cladodes with five wounds each. The same number of uninoculated cladode was used as control. The experiment was performed twice. Two weeks later, all inoculated cladodes showed necrotic symptoms, which were similar to the symptoms previously observed in the field. The uninoculated cladode remained symptomless. The fungus was reisolated from the inoculated cladode and its morphological characteristics were similar to the original isolate. has been reported to cause anthracnose on H. costaricensis in Mexico (Nunez-Garcia et al. 2023), , and (Evallo et al. 2022). For the best of our knowledge, this is the first report of anthracnose caused by in in Brazil.